The differences in the accuracy of various methods in calculating estimated fetal weight - Fathia Rizki; Irma Mulyati (Jurnal Kesehatan Ibu dan Anak, 2021)
Uterus fundus height measurement can be used as an indicator in the assessment of estimated fetal weight. Ideally, the measurement of the estimated fetal weight is measured using sophisticated equipment. However, in Indonesia, many deliveries are still carried out in basic services so limited by authority, its necessary to develop reliable but straightforward measurement techniques. The purpose of this research is to determine the differences in the results of the simple formula, the dare formula, and the Johnson Toshack in calculating the estimated fetal weight. This research is an analytical survey research with a cross-sectional approach. There were 160 mothers involved as samples who gave birth in June-October 2020 at the Batujajar Public Health Center who met the inclusion and exclusion criteria. The data obtained were analyzed using the T-test and multiple linear regression. The results showed that there was no difference between the calculation of the simple formula (p-value=0.188) and the dare formula (p-value = 0.734) in calculating the estimated fetal weight. There is a difference between the Johnson-Toshack formula's calculation with the newborn's actual weight (p-value=0.001). The regression test results showed that the dare formula is more accurate with an r=0.999. In conclusion, the dare formula is more accurate in calculating the estimated fetal weight